STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA ANAK TUNAGRAHITA - admin, admin; Firmansyah, Rizqy; Jamal, Moh. Yusup Saepuloh (THORIQOTUNA: Jurnal Pendidikan Islam, 2021)
This study aims to determine the learning strategies, implementation and efforts to improve learning strategies for Islamic religious education in mentally retarded children in SLB PLUS ABCD Binawarga. The method used in this research is qualitative method. The data collected in this study were participatory observation, unstructured interviews, and documentation. The analysis carried out in this study is through data reduction, data presentation, drawing conclusions and data verification. The results showed that (1) the learning strategy of Islamic Religious Education in mentally retarded children was good, the teacher also understood the characteristics of students in a very short period of time and was able to change learning strategies spontaneously following the flow of students and the level of focus on learning. (2) The implementation of Islamic religious education learning strategies for mentally retarded children, students become happy and cheerful about learning, knowledge is absorbed by students. (3) efforts to improve the learning strategy of Islamic religious education teachers are required to develop individual programs so that learning can be useful in social life.